Pengaruh Istri dalam Mencari Nafkah terhadap Kesejahteraan Keluarga - Andesma Andesma (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
His research discusses the influence of wives in earning a living on family welfare, where this research was made based on observations regarding wives who work to earn a living, who are the backbone of the family in order to meet all the needs of their respective households. The majority of the labor force for women always increases every year. Because of the big role that women play as housewives, most of them play a big role in the welfare of their families, from paying for housing, education and even food. The role of the husband as head of the household and the wife as a housewife must go hand in hand. The husband as head of the family is responsible for earning a living for the welfare of the family. On the other hand, as a housewife, the wife must have creativity in managing the family economy. And what needs to be understood is that in the household each husband and wife have their own roles. So that general conclusions can be drawn, namely: a. The husband is obliged to provide his wife with shelter and other support. b. The wife must follow her husband and live at her husband's place. The amount of maintenance obligations depends on the husband's discretion. So providing maintenance is based on the husband's ability, not the wife's request. Families are formed through the marriage process. Marriage is a pattern of behavior created by God for regeneration in the development of human life in a world that is always dynamic in accordance with the times. With marriage, a life together in the household is formed. The journey of a household is like an ark that sails across the vast ocean and goes through a long journey where winds and storms will definitely come which will become obstacles on the journey.Recently, the reality is that many households find it difficult to realize the goal of marriage. Many households are unhappy due to various problems such as disharmony, economics, infidelity and so on. It is often found in household life that husband and wife complain and complain to other people or to their family, as a result of not fulfilling the rights that must be obtained or not carrying out obligations from one of the parties. Lack of understanding and even ignorance of husband and wife regarding the rights and obligations in the household is often be the cause of disharmony and rifts in the household. In order to achieve a good household, individuals in the household should know each other, understand and carry out their respective rights and obligations.